THE IMPACT OF COMORBIDITIES ON COVID-19 SEVERITY IN PEDIATRIC PATIENTS: A SYSTEMATIC REVIEW - M. Hadi, (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background:Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has caused over 6 million deaths worldwide. Comorbidities like obesity, asthma, and neurological disorders are risk factors for severe illness in pediatric patients. The direct impact of COVID-19 on child mortality is limited, with only 0.4% of deaths occurring in children under 20.Objective: To identify risk factors and potential interventions to reduce severe illness and mortality in pediatric patients.Methods:A systematic review of COVID-19, sars-cov-2, and novel coronavirus in children was conducted using PubMed and Google Scholar. Severe COVID-19 prevalence in children assessed using Strengthening the Reporting of Observational Studies in Epidemiology (STROME) and the Joanna Briggs Institute (JBI) checklists, assessing quality and bias.Results:A review of 41 studies found a significant difference in severe COVID-19 infection risk among children with and without comorbidities, including hematologic, immune, respiratory, cardiovascular, neurological, obesity, and genetic syndromes.Conclusion:Comorbidities in pediatric COVID-19 patients enhance the risk; vaccinations and increased vigilance should take priority.